2008
DOI: 10.1016/j.jhazmat.2007.10.034
|View full text |Cite
|
Sign up to set email alerts
|

High temperature behavior of electrostatic precipitator ash from municipal solid waste combustors

Abstract: To cite this version:Lydie Le Forestier, Guy Libourel. High temperature behavior of electrostatic precipitator ash from municipal solid waste combustors. Journal of Hazardous Materials, Elsevier, 2008, 154, pp.373-380 AbstractMunicipal solid waste (MSW) flue gas residues require further treatment prior to disposal or reuse, and vitrification is one of the main solidification-stabilization processes. This paper investigates the high temperature behavior of MSW flue gas residues, performed in laboratory experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Comparison with the results of differential scanning calorimetry (DSC) revealed that the mass loss rate was the highest between 1050 and 1150 C, just before the initiation of overall melting. The DSC trace showed several endothermic peaks, which can be attributed to the decomposition of KCl, NaCl, Na 2 O, K 2 O, and alkaline metallic sulfates, and the evaporation of volatile metals (Tables 1 and 2), similar being reported by Le Forestier and Libourel (2008). The main melting process started just below 1200 C, as in other investigations (Cheng and Chen, 2004).…”
Section: Microstructures Of Fly Ash and Its Productssupporting
confidence: 80%
“…Comparison with the results of differential scanning calorimetry (DSC) revealed that the mass loss rate was the highest between 1050 and 1150 C, just before the initiation of overall melting. The DSC trace showed several endothermic peaks, which can be attributed to the decomposition of KCl, NaCl, Na 2 O, K 2 O, and alkaline metallic sulfates, and the evaporation of volatile metals (Tables 1 and 2), similar being reported by Le Forestier and Libourel (2008). The main melting process started just below 1200 C, as in other investigations (Cheng and Chen, 2004).…”
Section: Microstructures Of Fly Ash and Its Productssupporting
confidence: 80%
“…The processing of municipal waste fly ash causes both evaporation (Jakob et al 1995), as well as stabilization (Chou et al 2009) of heavy metals, depending on the ash treatment temperature. Cd and Pb are usually highly volatile (Jakob et al 1995), whereas Cu and Zn volatilization strongly depends on air quantity (Jakob et al 1995, Serum et al 2003, and Ni is not released during thermal treatment (Forestier and Libourel 2008). Their solubility is poor, therefore only a very limited quantity of heavy metals should be released into the aqueous solution through water leaching.…”
Section: Discussionmentioning
confidence: 99%
“…As for evaporation, the distribution ratios of metal elements in BFA are generally determined by volatility. For fine-grained fly ash, more than 90% of evaporation in air is obtained at 670 o C for Pb, 750 o C for Cd [16] , and the volatilization ratios of Cd and Pb from OFA are almost 100% during melting [17] . All the Cr deposits to slag [15,18] .…”
Section: Behavior Of Heavy Metalsmentioning
confidence: 99%